2011
DOI: 10.1891/2156-5287.1.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Intending and Achieving a Planned Home Birth in the United Kingdom: An Observational Study of 515,777 Maternities in the North West Thames Region, 1988–2000

Abstract: Background & objectives : This study aims to identify factors which have an independent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Of these 28% in the caseload group, only 2% gave birth at home. This statistic concurs with other studies findings which showed women planning to give birth at home were more likely to be older, white, have a fluent understanding of English, and live in a more socioeconomically advantaged area (Nove et al, 2011, ONS, 2013. Another recent study (Overgaard et al, 2012) found the effect of birth place did not differ with levels of social disadvantage, these findings suggest the benefits of birth outside obstetric units applies to women of all social demographics, but are not equally accessed.…”
Section: Birth Outcomes;supporting
confidence: 91%
“…Of these 28% in the caseload group, only 2% gave birth at home. This statistic concurs with other studies findings which showed women planning to give birth at home were more likely to be older, white, have a fluent understanding of English, and live in a more socioeconomically advantaged area (Nove et al, 2011, ONS, 2013. Another recent study (Overgaard et al, 2012) found the effect of birth place did not differ with levels of social disadvantage, these findings suggest the benefits of birth outside obstetric units applies to women of all social demographics, but are not equally accessed.…”
Section: Birth Outcomes;supporting
confidence: 91%
“…Women from the NZ cohort who planned to birth at home were more likely to be multiparous, older and with a lower BMI when compared to those women planning to birth in other settings. This replicates findings from the BPE cohort and several other observational studies (Birthplace in England Collaborative Group, 2011; Hildingsson, Lindgren, Haglund, & Radestad, 2006;MacDorman, Declercq, & Matthews, 2011;Nove, Berrington, & Matthews, 2011). In these developed countries (Sweden, America, UK), it would appear that women who plan to give birth at home are more likely to be multiparous, with a maternal age between 30 and 35 years of age, a high level of education, married or with a partner, and Caucasian or white.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of PPH for planned hospital births would be expected to be higher than the incidence for planned home births, because nulliparous women are more likely to experience PPH (see Table 2), and are also more likely to plan a hospital birth [28]. It was therefore not surprising to find that odds ratio was 2.7 before any adjustment was made for confounding.…”
Section: Discussionmentioning
confidence: 99%